Azadirachta Indica Phytoconstituents as Novel Inhibitors for Main Proteases of COVID-19: Molecular Dynamics and Simulation Study - Hussain, Ubaida; Gillani, Fatima; Gull, Laiba; Ahmad, Usman; Gull, Iram; Noreen, Saadia; Muhammad Imran (Indus Journal of Bioscience Research, 2025)
Objective: This study aimed to evaluate the therapeutic potential of Azadirachta indica phytoconstituents as inhibitors of SARS-CoV-2 main protease (Mpro) and papain-like protease (PLpro) using computational approaches. Methods: Twenty phytochemicals were screened using molecular docking with AutoDock Vina to determine binding affinities against Mpro (PDB: 6YB7) and PLpro (PDB: 7LBR). Molecular dynamics simulations were performed using the iMODS server to evaluate protein-ligand complex stability. ADMET analysis using SwissADME assessed pharmacokinetic properties, including gastrointestinal absorption, lipophilicity, and compliance with Lipinski's Rule of Five. Results: The highest binding affinities were observed with 7-deacetyl 7-benzoyl gedunin for Mpro (-9.7 kcal/mol) and PLpro (-8.2 kcal/mol). ADMET analysis showed satisfactory pharmacokinetics, with most ligands demonstrating good GI absorption and no blood-brain barrier permeability. Molecular dynamics confirmed stability, with low Eigenvalues (Mpro: 1.282, PLpro: 6.226). Conclusion: The phytoconstituents of Azadirachta indica demonstrated significant potential as inhibitors of SARS-CoV-2 proteases, supporting their role in antiviral drug development. Further experimental validation is recommended.